Cannabis combined with oxycodone for pain relief in fibromyalgia pain: a randomized clinical self-titration trial with focus on adverse events - van Dam, Cornelis Jan; Kramers, Cornelis; Schellekens, Arnt; Bouvy, Marcel; van Dorp, Eveline; Kowal, Mikael A.; Olofsen, Erik; Dahan, Albert; Niesters, Marieke; van Velzen, Monique (Frontiers in Pain Research, 2024)
ObjectivesWe determined whether adding cannabis to oxycodone for chronic non-cancer pain management could reduce treatment-related adverse effects (AEs) while maintaining effective analgesia.MethodsIn this open-label study, fibromyalgia patients aged ≥18 years were randomized to receive 5 mg oxycodone tablets (max. four times/day), 150 mg of inhaled cannabis containing 6.3% Δ9-tetrahydrocannabinol and 8% cannabidiol (max. times inhalation sessions/day), or a combination of both for 6 weeks. The primary endpoint was treatment-related adverse events, assessed using a 10-point composite adverse event (cAE) score; additionally, we recorded daily reported pain relief and daily tablet and cannabis consumption.ResultsIn total, 23 patients were treated with oxycodone, 29 with cannabis, and 29 with the oxycodone/cannabis combination. Three patients from the oxycodone group (13%) and 18 patients from the cannabis groups (31%, 9 in each group) withdrew from the trial within 2–3 weeks because of the severity of AEs. There were no differences in treatment-related cAE scores among the three groups that completed the study (p = 0.70). The analgesic responder rate showed a ≥1- point reduction in pain in 50% and a ≥2-point reduction in 20% of patients, while 50% of patients experienced no treatment benefit. The combination treatment reduced oxycodone tablet consumption by 35% (p = 0.02), but it did not affect the number of cannabis inhalation sessions.ConclusionsCannabis combined with oxycodone offered no advantage over either treatment alone, except for a reduction in opioid tablet intake; however, the overall drug load was the highest in the combination group. Moreover, cannabis was poorly tolerated and led to treatment discontinuation in one-third of participants treated with cannabis.Clinical Trial RegistrationThe trial was registered at the WHO International Clinical Trials Registry Platform (trialsearch.who.int) on July 26, 2019, identifier NL7902.